(untitled) (Herald of the National Children’s Medical Center, 2025)
Breast cancer (BC) remains one of the most common causes of cancer morbidity and mortality among women. The effectiveness of treatment largely depends on the accuracy of disease staging at the time of initial diagnosis. Positron emission tomography with ¹⁸F-fluorodeoxyglucose (¹⁸F-FDG PET/CT) has become a significant method of molecular imaging, capable of detecting not only the location of the primary tumor but also distant metastases that may not be visible with standard imaging modalities such as ultrasound, MSCT, or MRI.